Actuators 2018
DOI: 10.5772/intechopen.78572
|View full text |Cite
|
Sign up to set email alerts
|

Development of Resonators with Reversible Magnetostrictive Effect for Applications as Actuators and Energy Harvesters

Abstract: This chapter presents the methodology of designing and testing wideband actuators and energy harvesters which can be treated as one device called a mechanical resonator. In order to obtain described effects, the magnetostriction phenomenon was used. This effect enables the construction of resonators in selected frequency bands, including the ultrasonic range. Cores made of giant magnetostrictive materials (GMM) were used for the construction. Considerable attention was given to composite cores to reduce the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The number of core components (GMM rods, neodymium magnets, pressure mandrels) is of key significance for its construction, the fewer of them, the higher work frequencies are achieved. One of the solutions used in the core is a system made of alternately located neodymium magnets and Terfenol-D rods [3].…”
Section: Magnetostrictive Exciters Of Mechanical Vibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of core components (GMM rods, neodymium magnets, pressure mandrels) is of key significance for its construction, the fewer of them, the higher work frequencies are achieved. One of the solutions used in the core is a system made of alternately located neodymium magnets and Terfenol-D rods [3].…”
Section: Magnetostrictive Exciters Of Mechanical Vibrationmentioning
confidence: 99%
“…The authors have considerable experience in constructing actuators and magnetostrictive actuator harvesters [3], and their earlier research on the use of Terfenol-D have found a number of applications in exciters and vibration transducers [2,7,8].…”
Section: Magnetostrictive Exciters Of Mechanical Vibrationmentioning
confidence: 99%